Customer frustration incident and frustration behavior for priority plus program at Concorde Hotel Shah Alam / Siti Daleela Mohd Wahid - Mohd Wahid, Siti Daleela (Faculty of Business and Management, 2006)
The goal of the study is to reconfirm the "coffee talk" among the staff about this program. The staffs wonder whether this program needs to uphold or not in the future. The study interested to examine the negative effect of loyalty programs from the perspective of frustration theory. It seeks to develop a model of customer frustration based on frustration theory. For the methodology, firstly, frustration will be differentiated into two variables: frustration incident and frustration behavior. Secondly, a descriptive study and survey question among the members of Priority Plus Program is conducted. A correlation analysis will be used to identify the significant relationship between the variables. (Frustration incident and frustration behavior). Thirdly, the findings of the study are used to develop a system of hypotheses that generate a specific model of customer frustration in Priority Plus Program. For findings, there are three components of frustration incident (refusal of reward, reduction of reward and delay of reward) that were triggered by the Priority Plus Program lead directly to frustration behavior like protest and avoidance is identified. These also affect the perception of the relationship. in conclusion, Priority Plus Program tend to be uphold the program in order to fulfill the requirement of the loyal customer and avoid frustration among them.